(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2017)
The improvement of adolescent nutritional status may help address the reduction of all forms of malnutrition in Bangladesh. This is because at this stage, they experience a growth spurt thus increasing the need for most nutrients, needed for growth and reproductive health. The objective of this research was to assess the nutritional status of adolescent girls in rural areas of Bangladesh and find out the associated factors that affects nutritional status. A cross sectional study was carried out among 106 adolescent girls of Nobabpur village in Comilla district. A questionnaire was developed to obtain demographic information, food intake pattern and anthropometric measures such as weight, height with measuring instruments. About 80% were found normal according to BMI where about 13% adolescent girls were malnourished, below the cut off value 18.5. Place of residence, education of adolescent girls, their family expenditure to food and improper knowledge on food and nutrition were identified as underlying causes. Nutritional profiles of adolescent girl can be improved by implementing effective nutrition education program, providing supplementary food, facilitating primary health care program and creating awareness about nutritional knowledge. Severely malnourished adolescent girl in the selected area should be identified as early as possible and brought under supplementary feeding program. Bangladesh J. Sci. Ind. Res. 52(3), 221-228, 2017